The Influence of Entrepreneurial Orientation, Network, Market Orientation on Small Business Performance in West Java Province - Nugroho, Arief Teguh (The Eastasouth Management and Business, 2023)
This study aims to investigate the effect of entrepreneurial orientation (EO), network, and market orientation on the performance of small businesses (Small Business Performance) in West Java Province. Data was collected from 300 small business owners using a structured questionnaire. The results of multiple regression analysis show that the three independent variables have a significant positive effect on SBP. Market orientation has the strongest effect on SBP, followed by EO and network. The findings show that small business owners who have high levels of EO, network, and market orientation tend to perform better than those who have low levels of these characteristics. Small business owners in West Java Province can improve their performance by investing in developing EO capabilities, networks, and their market orientation. Future research can investigate the role of other variables, such as innovation, technology adoption, and strategic planning, on the performance of small businesses in West Java Province.